Polymer binder-coated electrodes for lithium-ion batteries
By using the granular polymer adhesive composition, the problems of poor adhesive performance and large usage caused by the adhesive solution form in the prior art are solved, and the electrode adhesion and battery performance are improved.
Patent Information
- Application Number
- JP2022538874
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-23
- Filing Date
- 2020-11-23
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2040-11-23
AI Technical Summary
In the prior art, when manufacturing electrodes of electrochemical equipment, the solution form of adhesive leads to poor adhesion performance and large amounts of use, which affects the adhesion of the electrode and the performance of the battery.
Using the particulate polymer binder composition, the electrode adhesion is significantly improved by controlling the particle size of more than 90% of the particulate polymer binder between 400 microns and 2.5 mm and having a significant density above 0.4 g/cc, combining the solvent and electrode material to form a coating with reduced consistency, which significantly improves the adhesion of the electrode.
The adhesion of the electrode and the performance of the battery are significantly improved, the amount of adhesive is used, and the fluidity and uniformity of the coating are improved by reducing consistency.
Smart Images

Figure 0007674359000006 
Figure 0007674359000007 
Figure 0007674359000008
Abstract
Description
[Technical field]
[0001] The present invention relates to polymeric binder compositions for use in coating electrochemical devices. [Background technology]
[0002] The electrodes are used in energy storage devices, including, but not limited to, batteries, capacitors, ultracapacitors, non-aqueous secondary batteries, and the like.
[0003] Currently, there are two primary means for manufacturing electrodes: the "wet" method and the "dry" method. In the wet method, a polymeric binder in the form of a solvent solution or dispersion is blended with one or more active powdered electrode-forming materials to form a slurry dispersion or paste. This dispersion or paste is then applied to one or both sides of a conductive substrate and dried to form a coherent composite electrode layer. The electrode layer can then be calendered. This method is shown in U.S. Pat. No. 5,776,637 and U.S. Pat. No. 6,200,703, where a fluoropolymer binder is dissolved in NMP. Summary of the Invention
[0004] Surprisingly, it has now been found that better adhesion can be achieved in the final battery product by using a polymer binder composition in granular form. Advantageously, the slurry made from the agglomerated fluoropolymer composition exhibits a lower viscosity and provides better adhesion to the electrodes.
[0005] Another advantage is improved binder dispersion and reduced binder usage.
[0006] The present invention relates to an improved method of making a battery electrode, comprising providing a granular polymer binder composition such that more than 90% by weight, preferably more than 95% by weight, of the particles of the granular polymer binder composition are 400 μm or more and less than 2.5 mm, preferably the granular binder composition has a raspberry morphology, combining the granular binder, a solvent and an electrode material to form a slurry, wherein said granular polymer binder composition is dissolved in a solvent, and coating the electrode substrate with the resulting slurry. Preferably, the polymer binder composition comprises a fluoropolymer composition, preferably a polyvinylidene fluoride polymer composition "PVDF". By using the granular polymer binder composition, the applicant has found that the polymer binder composition dissolves well, the polymer binder composition reduces the viscosity by at least 5% compared to the viscosity when using the same binder in powder form, and increases the peel strength of the cathode. The resulting electrodes made using the method of the present invention have better adhesion.
[0007] When the binder powder was compressed / granulated and then used in the process to fabricate the electrode, the slurry viscosity was unexpectedly reduced and the adhesion of the polymer binder composition to the electrode substrate was improved compared to when the same binder was used without granulation (used in powder form).
[0008] Applicants have discovered a method for improving adhesion in battery electrodes, the method comprising dissolving a particulate polymer binder composition, preferably comprising a fluoropolymer composition, preferably a polyvinylidene polymer composition, in a solvent to form a slurry, adding an electrode material to the slurry, and then coating an electrode substrate with the slurry comprising an active material. The particulate polymer binder composition is characterized in that its apparent density is greater than 0.4, preferably greater than 0.6, and more preferably greater than 0.8 g / cc, and the particulate polymer binder is composed of agglomerated particles having a raspberry morphology.
[0009] The present invention relates to a method for forming an energy storage device, a) dissolving a particulate polymeric binder, preferably a fluoropolymer composition, in a solvent to obtain a binder dispersion; b) combining the binder dispersion with an active powdered electrode-forming material to form a uniform blend; and c) applying the homogenous mixture to at least one surface of a conductive substrate to form an electrode; Including, wherein more than 90% of the granulated polymer binder particles are 400 μm or more and less than 2.5 mm, preferably 400-2000 microns, the bulk density of the polymer binder is greater than 0.4 g / cc, preferably greater than 0.6 g / cc, and the particles have a raspberry morphology. Particle size is measured by determining the % that pass through a screen of each mesh size.
[0010] The invention further relates to electrodes formed by this method that have better adhesion than binders formed from the same polymeric binder in powder form.
[0011] Aspects of the invention
[0012] Aspect 1: A method for producing a battery electrode, comprising: a. providing a granular polymeric binder composition, said binder composition comprising agglomerated particles, preferably having a raspberry morphology, greater than 95% by weight of the agglomerated particles being 400 μm or greater and less than 2.5 mm in size, and having a bulk density greater than 0.4 g / cc; b. combining a particulate polymer binder composition, a solvent, and an electrode material to provide an electrode-forming composition, wherein the polymer binder composition is dissolved in the solvent; c. applying the electrode-forming composition onto at least one surface of a conductive substrate; d. evaporating the organic solvent in the electrode-forming composition to form a composite electrode layer on the conductive substrate; A method comprising:
[0013] Aspect 2: Step (b) comprises b1. adding a granular polymer binder composition to an organic solvent; b2. mixing until dissolved to provide a solution of said particulate binder; b3. combining an electrode material with the solution of the particulate binder to provide an electrode forming composition; 2. The method of embodiment 1, comprising:
[0014] Aspect 3: The method of aspect 1 or 2, wherein the granular polymer binder composition comprises a polymer selected from the group consisting of fluoropolymers, SBR, ethylene vinyl acetate (EVA), acrylic polymers, polyurethanes, styrene polymers, polyamides, polyesters, polycarbonates, and thermoplastic polyurethanes (TPUs), and combinations thereof.
[0015]
[0023] Aspect 4: The method of aspect 1 or 2, wherein the particulate polymer binder composition comprises a fluoropolymer.
[0016] Aspect 5: The melt viscosity of the fluoropolymer is 450° F. (232° C.) and 100 s according to ASTM method D-3835. -1 The method of embodiment 4, wherein the tensile strength is greater than 5 kPoise, preferably greater than 15 kPoise, as measured at 1000 MPa.
[0017] Aspect 6. The method of aspect 4, wherein the fluoropolymer comprises a polyvinylidene fluoride polymer comprising at least 50% by weight vinylidene fluoride monomer units, preferably at least 75% by weight vinylidene fluoride monomer units.
[0018] Example 7: The method of example 4, wherein the fluoropolymer is a copolymer comprising vinylidene fluoride monomer units and from 1 to 30 weight percent of hexafluoropropene monomer units.
[0019] Example 8: The method of any one of Examples 1-7, wherein the electrode material comprises an active material selected from the group consisting of lithium and transition metal oxides, sulfides, or hydroxides; carbonaceous materials; nano titanates, and combinations thereof.
[0020]
[0023] Aspect 9. The method of aspect 8, wherein the electrode material further comprises a conductivity-imparting additive.
[0021] Example 10: The method of any one of Examples 1 to 7, wherein the electrode material comprises a carbonaceous material in the form of particles having an average diameter of 0.5 to 100 μm.
[0022]
[0023] Aspect 11. The method of any one of Aspects 1-10, wherein the agglomerated particles have a bulk density of 0.6 g / cc or greater.
[0023] Example 12: The method of any one of Examples 1-11, wherein the agglomerated particles are greater than 400 μm but less than 2000 μm.
[0024] Embodiment 13: An electrode formed by the method of any one of embodiments 1-12.
[0025] Example 14: A battery comprising an electrode produced by the method of any one of Examples 1 to 12. [Brief description of the drawings]
[0026] [Figure 1] FIG. 1 shows the fluoropolymer binder composition powder at a magnification of 70x. [Diagram 2] FIG. 2 shows the fluoropolymer binder composition powder at a magnification of 20,000 times. [Diagram 3] FIG. 3 shows the fluoropolymer binder composition powder at a magnification of 50,000 times. [Figure 4] FIG. 4 shows the granulated fluoropolymer binder composition at a magnification of 70×. [Diagram 5] FIG. 5 shows the granulated fluoropolymer binder composition at a magnification of 10,000 times. [Figure 6] FIG. 6 shows the granulated fluoropolymer binder composition at a magnification of 50,000 times. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] As used herein, copolymer refers to any polymer having two or more different monomer units, including terpolymers and those having more than three different monomer units.
[0028] Percentages used herein are weight percentages unless otherwise specified, and molecular weights are weight average molecular weight unless otherwise specified.
[0029] All references cited in this application are hereby incorporated by reference.
[0030] Raspberry structure is a material in which the particles are composed of smaller primary particles and are visible under a microscope. This structure / morphology is well known in the art.
[0031] Apparent density is a way to distinguish between powders and granules for a given polymer composition. Apparent density is the bulk density of a powder. It gives the mass per unit volume of a loosely packed powder. This value is the first low-cost evaluation of a powder to judge lot-to-lot consistency. A low apparent density may indicate (smaller) fine particles, a high apparent density large particles. Also, if the powder is heavily agglomerated, this may show up as an increase in apparent density. Bulk or apparent density is measured by gently introducing a known sample mass into a graduated cylinder and carefully flattening the powder without compressing it. The apparent volume before dabbing is then read to the nearest graduation unit.
[0032] By powder it is meant that more than 90% by weight of the particles have a particle size less than 300 microns, preferably less than 200 microns.
[0033] Slurry viscosity is measured at 25°C using a Brookfield viscometer. An SSA7R chamber is used with a spindle number of 15. The % solids of the slurry ranges from 40 to 87 weight percent. Viscosity can be measured at 71 to 72 weight percent solids.
[0034] The method of carrying out the present invention will be generally described with respect to a specific preferred embodiment, namely, polyvinylidene fluoride-based polymers prepared by aqueous emulsion polymerization. Although the invention has been generally described with respect to PVDF polymers, those skilled in the art will recognize that similar polymerization and application techniques are applicable to the preparation of other polymeric binder compositions.
[0035] The present invention provides a method of making a binder composition and a method of making an electrode comprising said binder composition, the method comprising the step of dissolving a particulate binder, wherein more than 90% by weight, preferably more than 95% by weight, of the particles of the particulate binder are between 400 microns and less than 2.5 mm, preferably between 400 microns and 2000 microns, and have an apparent density of more than 0.4 g / cc, preferably more than 0.6 g / cc. Particle size is measured by determining the weight percentage passing through a screen of each mesh size.
[0036] Surprisingly, it has been found that the use of a granular polymer binder composition results in lower slurry viscosity and increased adhesion of the slurry to the electrode substrate compared to using a powder form in which greater than 90% by weight of the particles are less than 300 microns.
[0037] The fluoropolymer polymer binder composition is preferably a fluoropolymer composition which may be a homopolymer or copolymer with or without functional groups. PVDF is the preferred fluoropolymer.
[0038] Compaction / granulation of polymers is well known in the art to reduce dust, control particle size, control bulk density, or improve dissolution / dispersion rates. See, for example, https: / / www.fitzpatrick-mpt.com and The Fitzpatrick Company's brochure "Roll Compaction RC-5 / 09" which describes granulation.
[0039] Fluoropolymer The term fluoropolymer means any polymer having in its chain at least one monomer selected from compounds containing a vinyl group that can open up to polymerize, and containing, directly bonded to this vinyl group, at least one fluorine atom, at least one fluoroalkyl group or at least one fluoroalkoxy group.
[0040] Useful fluoropolymers are thermoplastic homopolymers and copolymers having more than 50 weight percent fluoromonomer units, preferably more than 65 weight percent, more preferably more than 75 weight percent, and most preferably more than 90 weight percent of one or more fluoromonomers. Useful fluoromonomers for forming fluoropolymers include, but are not limited to, vinylidene fluoride (VDF or VF2), 1,2-difluoroethylene, trifluoroethylene (VF3); tetrafluoroethylene (TFE), trifluoroethylene (TrFE), chlorotrifluoroethylene (CTFE), hexafluoropropene (HFP), vinyl fluoride (VF), hexafluoroisobutylene (HFIB), perfluorobutylethylene (PFBE), pentafluoropropene, 3,3,3-trifluoro-1-propene, 2-trifluoromethyl-3,3,3-trifluoro ... perfluoromethyl ether (PMVE), perfluoroethyl vinyl ether (PEVE), perfluoropropyl vinyl ether (PPVE), perfluorobutyl vinyl ether (PBVE), fluorinated (alkyl) vinyl ethers including long chain perfluorinated vinyl ethers, fluorinated dioxoles such as fluorinated perfluoro(1,3-dioxole); perfluoro(2,2-dimethyl-1,3-dioxole) (PDD), C4 or higher partially or perfluorinated alpha olefins, C3 or higher partially or perfluorinated cyclic alkenes, and combinations thereof.
[0041] The present invention applies to thermoplastic fluoropolymers, homopolymers and copolymers. Preferred polymer binders include, but are not limited to, homopolymers of polyvinylidene fluoride and copolymers of polyvinylidene fluoride and hexafluoropropene (VDF-HFP).
[0042] Vinylidene fluoride polymers are used to illustrate the present invention and are the preferred polymers (including homopolymers and copolymers). Such copolymers include those in which at least 50% by weight, preferably at least 75% by weight, more preferably at least 80% by weight, and even more preferably at least 85% by weight of vinylidene fluoride is copolymerized with one or more comonomers. Exemplary comonomers are tetrafluoroethylene, trifluoroethylene, chlorotrifluoroethylene, hexafluoropropene, vinyl fluoride, pentafluoropropene, tetrafluoropropene, trifluoropropene, perfluoroethyl vinyl ether, and perfluorinated vinyl ethers such as perfluoro-2-propoxypropyl vinyl ether, perfluoromethyl vinyl ether, perfluoropropyl vinyl ether, and other monomers that readily copolymerize with vinylidene fluoride, as well as 3,3,3-trifluoro-1-propene, 1,2,3,3, The monomer units may be selected from the group consisting of one or more partially or fully fluorinated alpha olefins, such as 3-pentafluoropropene, 3,3,3,4,4-pentafluoro-1-butene, partially fluorinated olefin hexafluoroisobutylene, fluorinated dioxoles, such as perfluoro(1,3-dioxole) and perfluoro(2,2-dimethyl-1,3-dioxole), allyl, partially fluorinated allyl, or fluorinated allyl monomers, such as 2-hydroxyethyl allyl ether or 3-allyloxypropanediol, and ethene or propene. Other monomer units in these polymers may include any monomer that contains a polymerizable C=C double bond. Additional monomers may be 2-hydroxyethyl allyl ether, 3-allyloxypropanediol, allyl monomers, ethene or propene, acrylic acid, methacrylic acid.
[0043] In one embodiment, up to 30% by weight, preferably up to 25% by weight, more preferably up to 15% by weight, of hexafluoropropene (HFP) units and 70% by weight or more, preferably 75% by weight or more, more preferably 85% by weight or more of VDF units are present in the vinylidene fluoride polymer. In order to provide a PVDF-HFP copolymer with excellent dimensional stability in the end-use environment, it is desirable for the HFP units to be distributed as uniformly as possible.
[0044] The most preferred copolymers and terpolymers of the invention are those in which vinylidene fluoride units constitute greater than 50 percent, preferably at least 60 percent by weight, and more preferably greater than 70 percent by weight of the total weight of all monomer units in the polymer. Copolymers, terpolymers, and higher polymers of vinylidene fluoride can be prepared by reacting vinylidene fluoride with one or more monomers from the group consisting of vinyl fluoride, trifluoroethene, tetrafluoroethene, one or more partially or fully fluorinated alpha olefins such as 3,3,3-trifluoro-1-propene, 1,2,3,3,3-pentafluoropropene, 3,3,3,4,4-pentafluoro-1-butene, and hexafluoropropene, the partially fluorinated olefin hexafluoroisobutylene, perfluorinated vinyl ethers such as perfluoromethyl vinyl ether, perfluoroethyl vinyl ether, perfluoro-n-propyl vinyl ether, and perfluoro-2-propoxypropyl vinyl ether, fluorinated dioxoles such as perfluoro(1,3-dioxole) and perfluoro(2,2-dimethyl-1,3-dioxole), allyl, partially fluorinated allyl, or fluorinated.
[0045] Emulsification Process Fluoropolymers such as polyvinylidene-based polymers can be produced by any process known in the art using aqueous free radical emulsion polymerization, but suspension, solution and supercritical CO2 polymerization processes can also be used. Processes such as emulsion and suspension polymerization are preferred and are described in U.S. Patent Publication No. 6,187,885 and European Patent Publication No. 0,120,524. Emulsion polymerization is most preferred.
[0046] In a typical emulsion polymerization process, a reactor is charged with deionized water, a water-soluble surfactant capable of emulsifying the reaction mass during polymerization, and an optional paraffin wax antifouling agent. The mixture is stirred and deoxygenated. A predetermined amount of a chain transfer agent, CTA, is then introduced into the reactor, the reactor temperature is raised to a desired level, and monomers (e.g., vinylidene fluoride and possibly one or more comonomers) are fed into the reactor. Once the initial charge of monomers has been introduced and the pressure in the reactor has reached a desired level, an initiator is introduced to start the polymerization reaction. The temperature of the reaction may vary depending on the characteristics of the initiator used, and those skilled in the art will know how to do so. Typically, the temperature is about 30° to 150° C., preferably about 60° to 120° C. Once the desired amount of polymer in the reactor has been reached, the monomer feed is stopped, but the initiator feed is optionally continued to consume the residual monomer. The residual gas (including unreacted monomer) is vented, and the latex is recovered from the reactor.
[0047] The surfactant used in the polymerization can be any surfactant known in the art to be useful in PVDF emulsion polymerization, including perfluorinated, partially fluorinated, and non-fluorinated surfactants. Preferably, the PVDF emulsion is free of fluorosurfactants and no fluorosurfactants are used in any part of the polymerization. Non-fluorinated surfactants useful in PVDF polymerization can be both ionic and non-ionic in nature, including, but not limited to, 3-allyloxy-2-hydroxy-1-propanesulfonates, polyvinylphosphonic acid, polyacrylic acid, polyvinylsulfonic acid and their salts, polyethylene glycol and / or polypropylene glycol and their block copolymers, alkylphosphonates, and siloxane-based surfactants.
[0048] The polymerization generally results in a latex having a solids level of from 10 to 60 weight percent, preferably from 10 to 50 percent, and a weight average particle size of less than 500 nm, preferably less than 400 nm, more preferably less than 300 nm. The weight average particle size is generally at least 20 nm, preferably at least 50 nm.
[0049] For use in the present invention, the latex is spray dried to a powder form and the powder is then granulated so that more than 90% by weight, preferably more than 95% by weight, of the agglomerated (granular) particles are greater than 400 μm and less than 2.5 mm, preferably between 400 and 2000 microns, and have a bulk density greater than 0.4 g / cc, preferably greater than 0.6 g / cc. The granular particles have a raspberry morphology.
[0050] The polymer binder composition of the present invention is any thermoplastic polymer typically used as an electrode binder. The polymer is typically a semi-crystalline polymer.
[0051] In some embodiments, the binder is a fluoropolymer composition and has a melting point greater than 100°C, preferably greater than 145°C, preferably greater than 155°C.
[0052] The fluoropolymer composition used in the electrode composition is preferably of high molecular weight. As used herein, high molecular weight means a polymer that can be fused at 450° F. (232° C.) and 100 s according to ASTM method D-3835. -1 By "melt viscosity" is meant a fluoropolymer (preferably PVDF) having a melt viscosity, measured by the FTIR, of greater than 10 kpoise, preferably greater than 15 kpoise, more preferably greater than 20 kpoise, and most preferably greater than 25 kpoise.
[0053] Electrode Slurry The cathode-forming slurry includes a solvent, electrode materials (including a cathode active material and a conductive material), and a polymer binder. The anode-forming slurry includes a solvent, electrode materials (including an anode active material), and a polymer binder.
[0054] Slurry Solvent Any suitable organic solvent that dissolves the polymer binder can be used. The organic solvent used to dissolve the polymer binder composition (preferably a fluoropolymer, more preferably a vinylidene fluoride polymer composition) to provide the binder solution according to the present invention can be preferably polar. Examples of organic solvents include N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone, dimethylformamide, N,N-dimethylacetamide, N,N-dimethylsulfoxide, hexamethylphosphamide, dioxane, tetrahydrofuran, tetramethylurea, triethyl phosphate, and trimethyl phosphate. These solvents can be used alone or in combination of two or more. The particulate polymer binder composition can be dissolved in a solvent to make the polymer binder solution.
[0055] electrode material The electrode-forming composition can be obtained by adding and dispersing the electrode material (active material and optional additives such as a conductivity-imparting additive) together with the polymer binder according to the present invention and a solvent to give an electrode-forming slurry. The electrode material is preferably in dry powder form. Preferably, the granular polymer binder composition is first dissolved in a solvent (to provide a binder solution) and then the electrode material is added.
[0056] When forming a positive electrode (cathode), the electrode material includes a cathode active material and a conductivity-imparting additive (conductive material).When forming a negative electrode (anode), the electrode material includes an anode active material, preferably a carbonaceous material.
[0057] When forming a positive electrode (cathode), the cathode active material may contain a complex metal chalcogenide represented by the general formula LiMY2. Here, M represents at least one type of transition metal such as Co, Ni, Fe, Mn, Cr, and V; Y represents a chalcogen such as O or S. Among these, it is preferable to use a lithium-based complex metal oxide represented by the general formula LiMO2 (wherein M is the same as above). Preferred examples include LiCoO2, LiNiO2, LiNi x CO 1-x Among these, the formula LiNiO2 and the spinel structure LiMn2O4 are the most popular because of their high charge / discharge potential and excellent cycle characteristics. x Co 1-x It is particularly preferable to use Li-Co or Li-Ni binary composite metal oxides or Li-Ni-Co ternary composite metal oxides represented by the formula: LiCoO2 (0≦x≦1). The cathode active material is not limited to, but may be LiCoO2, LiNi 1-x Co x O2, Li 1-x Ni 1-y Co y O2, LiMO2 (M = Mn, Fe), Li[Ni x Co 1-2x Mn x ]O, LiNi x Mn y Co zO2, LiM2O4 (M=Ti, V, Mn), LiM x Mn 2-x O4(M=Co 2+ , Ni 2+ , Mg 2+ , Cu 2+ , Zn 2+ , Al 3+ , Cr 3+ ), LiFePO4, LiMPO4 (M=Mn, Co, Ni), LiNi x Co y Al z Preferred positive electrode materials include, but are not limited to, LiCoO2, LiNi x Co 1-x O2, LiMn2O4, LiNiO2, LiFePO4, LiNi x Co y Mn z O m , LiNi x- Mn y Al z O m where x+y+z=1 and m is an integer representing the number of oxygen atoms in the oxide to provide an electron-balanced molecule. Lithium metal oxides include lithium cobalt oxide, lithium iron phosphate, lithium manganese phosphate, lithium nickel oxide, and lithium manganese oxide.
[0058] When forming a positive electrode (cathode), a conductivity-imparting additive can be added to improve the conductivity of the composite electrode layer formed by applying and drying the electrode-forming composition of the present invention. Such a conductivity-imparting additive can be used in an amount of preferably 0 to 10 parts by weight, and optionally 0.1 to 10 parts by weight, based on 100 parts by weight of the active material constituting the positive electrode (cathode). The conductive agent is not limited, but may be carbonaceous materials such as graphite, graphite fine powder or fiber, carbon black, ketjen black, carbon fiber, carbon nanotube, and acetylene black, or fine powder or fiber of metals such as nickel or aluminum. The conductive carbon black preferably has an average particle size (diameter) of 10 to 100 nm as determined by electron microscope observation.
[0059] When forming a negative electrode (anode), the electrode material (active material) preferably includes a carbonaceous material such as graphite, activated carbon or a carbonaceous material obtained by carbonization of a phenolic resin, and pitch.
[0060] The slurry may contain other additives. Such additives are known to those skilled in the art. The binder composition of the present invention may optionally contain additives, based on the polymer, from 0 to 15 weight percent, preferably from 0.1 to 10 weight percent, including, but not limited to, thickeners, pH adjusters, acids, rheological additives, anti-settling agents, surfactants, wetting agents, fillers, defoamers, and temporary adhesion promoters. Additional adhesion promoters may also be added to improve bonding properties and provide irreversible connectivity.
[0061] Formation of electrodes The slurry composition for forming a positive electrode or a negative electrode can be used to form an electrode structure. More specifically, the slurry composition can be applied to at least one side, preferably both sides, of a conductive substrate. The conductive substrate includes a metal foil or wire mesh such as iron, stainless steel, steel, copper, lithium, aluminum, nickel, silver, or titanium, and has a thickness of, for example, 5 to 100 μm or 5 to 20 μm for a small battery, and is dried at, for example, 50 to 170° C. to form a composite electrode layer with a thickness for a small battery of, for example, 10 to 1000 μm, preferably 10 to 200 μm, to provide an electrode structure for a non-aqueous battery.
[0062] The components of the slurry are combined to form a homogeneous slurry. Exemplary equipment used to combine the components includes, but is not limited to, a ball mill, a magnetic stirrer, a planetary mixer, a high-speed mixer, a homogenizer, and a static mixer. Those skilled in the art can select the appropriate equipment for the purpose. To obtain the polymer binder solution according to the present invention, it is preferable to dissolve about 0.1 to 20 parts by weight, particularly 1 to 15 parts by weight, of the granulated polymer binder composition in 100 parts by weight of a solvent. If the amount is less than 0.1 parts by weight, the proportion of the polymer in the solvent is too small, and sufficient binder performance may not be exhibited. If the amount is more than 20 parts by weight, the solution viscosity is likely to be high, making it difficult to prepare the electrode-forming slurry composition.
[0063] Preferably, the solids content (%) of the slurry is in the range of 40 to 87% by weight, more preferably about 50 to 85% by weight.
[0064] The cathode formulation between the active material, conductive agent, and polymer binder can vary. The amount of active material is preferably about 90-99% by weight, the amount of conductive agent is about 0.5-5% by weight, and the amount of polymer binder is about 0.5-5% by weight based on the total weight of the active material, conductive agent, and polymer binder composition.
[0065] The anode formulation includes a conductive agent and a polymer binder, the amount of the binder in the anode being about 0.5 to 5 weight percent, based on the total weight of the anode active material and the polymer binder composition.
[0066] Purpose Electrodes formed by the methods of the present invention can be used to form electrochemical devices, including, but not limited to, batteries, capacitors, and other energy storage devices.
[0067] More specifically, a secondary battery basically includes a laminated structure including a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode. The separator includes a microporous membrane of a polymer material, such as PVDF, polyethylene, or polypropylene, impregnated with an electrolyte. The non-aqueous electrolyte impregnated in the separator may include an electrolyte, such as a lithium salt, dissolved in a non-aqueous solvent (organic solvent). Examples of electrolytes may include LiPF6, LiAsF6, LiClO4, LiBF4, CH3SO3Li, CF3SO3Li, LiN(SO2CF3)2, LiC(SO2CF3)3, LiCl, and LiBr. Examples of organic solvents for such electrolytes may include, but are not limited to, propylene carbonate, ethylene carbonate, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, γ-butyrolactone, methyl propionate, ethyl propionate, and mixtures thereof. EXAMPLES
[0068] Test Method: The particle size of the activated carbon is measured using a TYLER RX-29 sieve shaker.
[0069] Working Example: Cathode Slurry Preparation The cathode slurry formulation is composed of an organic solvent, such as N-methyl-2-pyrrolidone (NMP) or N-ethyl-2-pyrrolidone, at least one cathode active material, at least one conductive material, and a polymer binder composition.
[0070] A Dispermat (BYK-Gardner) is used for laboratory scale mixing.
[0071] Example 1. Li[Ni 0.6 Co 0.2 Mn 0.2 ]O2 / Super P / Kynar® HSV900=96 / 2 / 2 Preparation of binder solution
[0072] For Kynar® HSV900 (granulated), over 90% of the particles are between 400 microns and 2 mm.
[0073] For Kynar® HSV900 (control), over 90% by weight of the particles are between 5 and 30 microns.
[0074] A 500 mL stainless steel vessel was filled with 300 g NMP and 27 g PVDF. The vessel was filled with NMP first, then HSV900 (granulated) or Kynar® HSV900 was added to the top. The difference in mixing efficiency between granulated and fine powders was immediately observed when mixing started. Fine powders form gel-like balls on the surface, which are difficult to soak into NMP. In contrast, HSV900 (granulated) showed superior mixing behavior due to its higher bulk density than fine powder. NMP and PVDF were mixed at 60 °C for 1 h using a Dispermat (BYK Gardner) mixer. The solutions were then cooled. To check the dissolution efficiency, the solids content was checked. Solids content measurements are performed using a Mettler Toledo ME204. An aliquot of each solution is placed in a 160 °C oven for 1 h.
[0075] [Table 1]
[0076] Viscosity measurements were performed using a Brookfield viscometer at 25° C. An SSA7R chamber was used, with a spindle number of 15.
[0077] [Table 2]
[0078] Preparation of cathode slurry
[0079] 10 g of Super P (conductive carbon black from TIMCAL) and 111 g of 9 wt% PVDF solution were added to a 500 mL stainless steel vessel. Ambient mixing was performed for 1 minute. 480 g of NMC622 was added to the vessel and mixed for 1 minute. Finally, the rotation speed was increased to achieve the desired slurry. The rotation speed was between 2000 rpm and 4000 rpm. After 1 hour, the resulting slurry was analyzed for slurry viscosity, peel, and solids. Additional solvent was added to obtain solids.
[0080] [Table 3]
[0081] [Table 4]
[0082] The slurry viscosity gives unexpected results as shown in Table 4. Viscosity measurements were performed at 25° C. using a Brookfield viscometer. A SSA7R chamber was used with a spindle number of 15. Although the only difference between Kynar® HSV900 (granulated) and Kynar® HSV900 is the bulk density, the resulting slurries show completely different rheological behavior. It shows that the mixing efficiency during the solution preparation process affects the overall behavior of the cathode slurry.
[0083] [Table 5]
[0084] Then the slurry was cast onto an aluminum foil current collector. The thickness can vary from 50um to 100um, but 70um is more preferable in laboratory tests. The coated current collector was placed in an oven at 120℃ for 30 minutes. Finally, the resulting cathode was compressed by a roll press machine. Cool press. The compression ratio is 20-30% (100um->70-80um).
[0085] To test the 180 degree peel, the cathode is cut into strips 1 inch wide and 15 cm long. Double-sided tape is applied to the substrate. Then, the strip is placed on one side of the tape for peel testing. Finally, the peel tester records the load applied to detach the cathode from the tape. Only relative values are given here as the values themselves may vary depending on the peel tester supplier, current collector, and peel tester head speed. Interestingly, Kynar HSV900 (granulated), which has better dissolution efficiency, shows higher peel than Kynar HSV900.
[0086] Figures 1-3 show fluoropolymer powders. These figures show that the powders are aggregates of individual primary particles that make up one powder particle. The average size of the powder particles in the figures is about 1 to 50 microns. Figures 4-6 show that the average size of the granulated fluoropolymer is over 400 microns and is made of aggregated primary particles. The SEM figures show that the granulation process does not change the shape of the individual PVDF particles. Granulation increases the bulk density.
Claims
1. A method for manufacturing a battery electrode, comprising the steps of: a. providing a granular polymeric binder composition, said binder composition comprising agglomerated particles, greater than 95% by weight of the agglomerated particles being 400 μm or greater and less than 2.5 mm in size, and having a bulk density greater than 0.4 g / cc; b. combining a particulate polymer binder composition, a solvent, and an electrode material to provide an electrode-forming composition, wherein the polymer binder composition is dissolved in the solvent; c. applying the electrode-forming composition onto at least one surface of a conductive substrate; d. Evaporating the solvent in the electrode-forming composition to form a composite electrode layer on the conductive substrate; A method comprising:
2. Step (b) b1. Adding a granular polymer binder composition to an organic solvent; b2. mixing until dissolved to provide a solution of said granular polymer binder composition; b3. combining an electrode material with the solution of the granular polymer binder composition to provide an electrode-forming composition; The method of claim 1 , comprising:
3. 2. The method of claim 1, wherein the granular polymer binder composition comprises a polymer selected from the group consisting of fluoropolymers, SBR, ethylene vinyl acetate (EVA), acrylic polymers, polyurethanes, styrene polymers, polyamides, polyesters, polycarbonates, and thermoplastic polyurethanes (TPUs), and combinations thereof.
4. The method of claim 1 , wherein the particulate polymer binder composition comprises a fluoropolymer.
5. The method of claim 2 , wherein the particulate polymer binder composition comprises a fluoropolymer.
6. The melt viscosity of the fluoropolymer is at 450° F. (232° C.) and 100 s according to ASTM method D-3835. -1 The method of claim 4, wherein the tensile strength is greater than 5 kPoise, as measured at 1000 K.
7. The method of claim 4 , wherein the fluoropolymer comprises a polyvinylidene fluoride polymer containing at least 50% by weight vinylidene fluoride monomer units.
8. The method of claim 4, wherein the fluoropolymer is a copolymer comprising vinylidene fluoride monomer units and from 1 to 30 weight percent hexafluoropropene monomer units.
9. 9. The method of any one of claims 1 to 8, wherein the electrode material comprises an active material selected from the group consisting of lithium and transition metal oxides, sulfides or hydroxides; carbonaceous materials; nano titanates and combinations thereof.
10. The method of claim 9 , wherein the electrode material further comprises a conductivity-imparting additive.
11. A method according to any one of the preceding claims, wherein the electrode material comprises a carbonaceous material in the form of particles having an average diameter of 0.5 to 100 μm.
12. The method of any one of claims 1 to 8, wherein the agglomerated particles have a bulk density of 0.6 g / cc or greater.
13. A method according to any one of claims 1 to 8, wherein the agglomerated particles are greater than 400 μm but less than 2000 μm.
14. An electrode formed by the method of any one of claims 1 to 13.
15. A battery comprising an electrode produced by the method of any one of claims 1 to 13.
16. The method of claim 4, wherein the fluoropolymer has a melt viscosity greater than 15 kPoise, measured according to ASTM method D-3835 at 450° F. (232° C.) and 100 s −1 .
17. The method of claim 4, wherein the fluoropolymer comprises a polyvinylidene fluoride polymer containing at least 75% by weight of vinylidene fluoride monomer units.
Citation Information
Patent Citations
Battery binder composition, battery electrode slurry, lithium secondary battery electrode, and lithium secondary battery
JP1999149929A
Nonaqueous electrolyte secondary battery
JP2006228515A
Solvent-free electrode manufacturing
JP2017525087A
Binder composition for secondary-battery electrode, slurry composition for secondary-battery electrode, secondary-battery electrode, and secondary battery
WO2016035286A1
Binder particle aggregate for electrochemical element electrode, slurry composition for electrochemical element electrode, method for manufacturing these, electrode for electrochemical element, and electrochemical element
WO2017195784A1